2010
DOI: 10.1007/s00436-010-1728-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential identification of Entamoeba spp. based on the analysis of 18S rRNA

Abstract: Entamoeba histolytica is known to cause intestinal and extra-intestinal disease while the other Entamoeba species are not considered to be pathogenic. However, all Entamoeba spp. should be reported when identified in clinical samples. Entamoeba polecki, Entamoeba coli, and Entamoeba hartmanii can be differentiated morphologically from E. histolytica, but some of their diagnostic morphologic features overlap. E. histolytica, Entamoeba dispar, and Entamoeba moshkovskii are morphologically identical but can be di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…Most molecular diagnostic tools detect only E. histolytica and do not detect other morphologically identical or similar species, giving rise to several questions. A previous study has already demonstrated a situation in which samples that were positive by microscopic examination for the E. histolytica / E. dispar complex were identified as E. hartmanni after analysis by two different molecular methods [20]. To avoid this potential confusion and provide complete epidemiologic data on parasitic infections, it is important to develop a reliable system for the identification and differentiation of pathogenic and nonpathogenic parasites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most molecular diagnostic tools detect only E. histolytica and do not detect other morphologically identical or similar species, giving rise to several questions. A previous study has already demonstrated a situation in which samples that were positive by microscopic examination for the E. histolytica / E. dispar complex were identified as E. hartmanni after analysis by two different molecular methods [20]. To avoid this potential confusion and provide complete epidemiologic data on parasitic infections, it is important to develop a reliable system for the identification and differentiation of pathogenic and nonpathogenic parasites.…”
Section: Discussionmentioning
confidence: 99%
“…For E. hartmanni , however, a cloning procedure was necessary to obtain a positive control because a protozoan culture of E. hartmanni was not available. For this process, positive DNA samples characterized in a previous study were used [20]. The specific E. hartmanni sequence was amplified with primers EhartF and EhartR2; this fragment was then cloned using the pCR 2.1-TOPO vector as described in the protocol with the pCR 2.1-TOPO TA Cloning Kit (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, E. histolytica is the only pathogenic species (201,236,351). Improvements in the understanding of the biochemical, immunological, and genetic differences of the members of this genus have resulted in the confirmation of three species, E. histolytica, E. dispar, and E. moshkovskii, that are morphologically identical in both their cyst and trophozoite stages (41,169).…”
Section: Entamoeba Speciesmentioning
confidence: 99%
“…Finally, the identification of Entamoeba spp. was done as previously reported [15]. All PCRs were carried out in a 25 μL volume containing 12.5 μL of PCR master mix 2X (Promega Italia, Milan, Italy), 100-200 ng of template DNA, and 0.6 mM of each primer.…”
Section: Fecal Dna Extractionmentioning
confidence: 99%